Role of the FOXM1/CMA/ER stress axis in regulating the progression of nonalcoholic steatohepatitis - Shuoyi Ma; Erzhuo Xia; Miao Zhang; Yinan Hu; Siyuan Tian; Xiaohong Zheng; Bo Li; Gang Ma; Rui Su; Keshuai Sun; Qingling Fan; Fangfang Yang; et al. (Clinical and Translational Medicine)
Abstract Background/aims The molecular mechanisms driving nonalcoholic steatohepatitis (NASH) progression are poorly understood. This research examines the involvement of chaperone‐mediated autophagy (CMA) in NASH progression. Methods Hepatic CMA activity was analysed in NASH mice and patients. Lysosome‐associated membrane protein 2A (LAMP2A) was knocked down or overexpressed to assess the effects of hepatocyte‐specific CMA on NASH progression. Mice received a high‐fat diet or a methionine and choline‐deficient diet to induce NASH. Palmitic acid was employed to mimic lipotoxicity‐induced hepatocyte damage in vitro. The promoter activity of FOXM1 was evaluated via ChIP and dual‐luciferase reporter assays. Results Hepatic CMA activity was substantially low in NASH mice and patients. LAMP2A knockdown resulted in hepatocyte‐specific CMA deficiency, which promoted fibrosis and hepatic inflammation in NASH mice. Both in vitro and in vivo, CMA deficiency also exacerbated hepatocyte damage and endoplasmic reticulum (ER) stress. Mechanistically, CMA deficiency in hepatocytes increased cholesterol accumulation by blocking the degradation of 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMGCR), a key cholesterol synthesis‐related enzyme, and the accumulated cholesterol subsequently induced ER stress and hepatocyte damage. The restoration of hepatocyte‐specific CMA activity effectively ameliorated diet‐induced NASH and ER stress in vivo and in vitro. FOXM1 directly bound to LAMP2A promoter and negatively regulated its transcription. The upregulation of FOXM1 expression impaired CMA and enhanced ER stress, which in turn increased FOXM1 expression, resulting in a vicious cycle and promoting NASH development. Conclusions This study highlights the significance of the FOXM1/CMA/ER stress axis in NASH progression and proposes novel therapeutic targets for NASH. Key points Chaperone‐mediated autophagy (CMA) deficiency in hepatocytes promotes hepatic inflammation and fibrosis in mice with nonalcoholic steatohepatitis (NASH) by inducing cholesterol accumulation and endoplasmic reticulum (ER) stress. Upregulated FOXM1 impairs CMA by suppressing the transcription of lysosome‐associated membrane protein 2A (LAMP2A), a rate‐limiting component of CMA. ER stress increases FOXM1 expression and cholesterol accumulation. FOXM1/CMA/ER stress axis forms a vicious circle and promotes the development of NASH.